The Development of Integrate Curriculum, Turath Studies Program of Private Islamic Schools in Rueso District, Narathiwat Province - Sulong, Abdulramae; Haengyama, Muhamadsuhaimi; Suwanno, Phimpawee; Nesalaeh, Muhammad (MENARA : Journal of Islamic and Contemporary Issues, 2024)
The present document research and field research aimed 1) to study the necessity of the integrate curriculum, turath studies program (TSP), in Rueso District, Narathiwat Province 2) to develop and find the effectiveness of the TSP program, and 3) to evaluate the satisfaction of using TSP program, in a private Islamic school. This research is a research and development with a total population of 400, consisting of 50 of secondary Islamic studies and 350 students of private Islamic schools in Rueso District, Narathiwat Province, who were studying at the secondary Islamic studies. The total sample of 36 people consisted of 5 school administrators, 8 of secondary Islamic studies teachers and students of Totanyong School, Rueso District, Narathiwat Province, who were studying in the first year of secondary Islamic studies, totaling 23 people. The research instruments consisted of 1) the needs assessment of TSP program, 2) TSP program quality assessment form, and 3) the satisfaction form of TSP program. The statistics used to analyze the data were percentage, mean ( ) and standard deviation (S.D.). The results showed that 1) the necessary for the implementation of the TSP program in the private Islamic school in Ruso district, Narathiwat province, was at the highest level ( =4.5 2) the quality of the TSP program in the private Islamic school in Ruso district, Narathiwat province was at the highest level ( =4.88). 3) the satisfaction of those who have tried the TSP program in the private Islamic schools in Rueso District, Narathiwat Province was at a high level which has an average equal to ( =4.44).